2022
DOI: 10.1002/mds.29025
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Deficiency Impairs Mitochondrial DNA Dynamics and Propagates Inflammation

Abstract: A BS TRACT: Background: Mutations in the E3 ubiquitin ligase parkin cause autosomal recessive Parkinson's disease (PD). Together with PTEN-induced kinase 1 (PINK1), parkin regulates the clearance of dysfunctional mitochondria. New mitochondria are generated through an interplay of nuclear-and mitochondrial-encoded proteins, and recent studies suggest that parkin influences this process at both levels. In addition, parkin was shown to prevent mitochondrial membrane permeability, impeding mitochondrial DNA (mtDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…For instance, exogenous expression of the water forming NADH dehydrogenase from Lactobacillus brevis (LbNOX) can restore the cellular NAD + /NADH balance and has been used to establish metabolic consequences of a low NAD + /NADH ratio in the setting of OXPHOS deficiency 19 . Expressing the NADH dehydrogenase in Parkin‐deficient cells would test whether the low NAD + /NADH ratio is responsible for the defects in mitochondrial biogenesis and cytosolic mtDNA leak observed by Wasner et al 8 or merely coincident. Likewise, expressing LbNOX in the Parkin KO; mutator mouse could establish whether the low NAD + /NADH ratio is responsible for DA neuronal loss in this model.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, exogenous expression of the water forming NADH dehydrogenase from Lactobacillus brevis (LbNOX) can restore the cellular NAD + /NADH balance and has been used to establish metabolic consequences of a low NAD + /NADH ratio in the setting of OXPHOS deficiency 19 . Expressing the NADH dehydrogenase in Parkin‐deficient cells would test whether the low NAD + /NADH ratio is responsible for the defects in mitochondrial biogenesis and cytosolic mtDNA leak observed by Wasner et al 8 or merely coincident. Likewise, expressing LbNOX in the Parkin KO; mutator mouse could establish whether the low NAD + /NADH ratio is responsible for DA neuronal loss in this model.…”
mentioning
confidence: 99%
“…Lowered NAD + suppresses PGC1‐α signaling by decreasing the activity of SIRT1, an NAD + ‐dependent deacetylase 10 . Although Wasner et al 8 do not directly measure NAD + and NADH, a recent study found that the NAD + /NADH ratio is decreased in PRKN KO and patient iDA neurons, 11 and both studies found an increase in the lactate/pyruvate ratio, 8,11 which is metabolically coupled to the NAD + /NADH ratio. Based on these findings, the authors suggest that Parkin deficiency may decrease mitochondrial biogenesis through lowered NAD + , via the SIRT1–PGC1‐α/NRF1–TFAM signaling axis.…”
mentioning
confidence: 99%
See 3 more Smart Citations